CLOCKWORK ORANGE Enhances PERIOD Mediated Rhythms in Transcriptional Repression by Antagonizing E-box Binding by CLOCK-CYCLE - Zhou, Jian; Yu, Wangjie; Hardin, Paul E. (PLOS Genetics, 2016)
Author Summary Circadian clocks control daily rhythms in animal, plant and fungal physiology, metabolism and behavior via transcriptional feedback loops. In Drosophila, the CLOCK-CYCLE (CLK-CYC) activator complex binds E-box regulatory sequences to initiate transcription of hundreds of effector genes including their own repressors, PERIOD (PER) and TIMELESS (TIM), which feed back to repress CLK-CYC until they are degraded, thus allowing another cycle of CLK-CYC activation. Although the repression process is critical for the stability and accuracy of circadian timekeeping, how PER-TIM complexes maintain a transcriptionally repressed state for many hours is not well understood. Here we demonstrate that the transcription factor CLOCKWORK ORANGE (CWO) antagonizes CLK-CYC E-box binding, thus enhancing the removal of CLK-CYC from E-boxes to maintain transcriptional repression. This process requires PER, which suggests that PER-TIM and CWO cooperate to maintain a transcriptionally repressed state by removing CLK-CYC from E-boxes. These results demonstrate that PER-TIM requires CWO to effectively repress circadian transcription, and given that circadian transcriptional regulators are well conserved, this mechanism may function to repress transcription in other animals including humans.